THE IMPORTANCE-PERFORMANCE ANALYSIS OF COMPENSATION PROGRAMS AT FREEPORT INDONESIA MIMIKA - Claudia Glory; David P. E. Saerang; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2023)
This study aims to analyze the importance and performance of compensation programs received by the employees of PT Freeport Indonesia, Mimika. This research uses quantitative approach with 100 employees of PT Freeport Indonesia, Mimika as respondents. There 9 total criteria in this research, which is: Salary, Overtime Pay, Incentive, Transportation, Meal Allowance, Annual Leave, Religious Holiday, Health Insurance, and Pension. The result of this research shows that Salary, Pension, and Annual Leave are in Quadrant I; Transportation, Religious Holiday, and Health Insurance are in Quadrant II; Meal Allowance and Overtime Pay in Quadrant III; following by Incentive in Quadrant IV. So, related with the findings in this research, there are some recommendations for PT Freeport Indonesia. Keywords: compensation, importance-performance analysis